2016
DOI: 10.1371/journal.pone.0148137
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Induces Dose-Dependent Chemotaxis or Fugetaxis of T-ALL Blasts through S1P1 Activation

Abstract: Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid involved in several physiological processes including cell migration and differentiation. S1P signaling is mediated through five G protein-coupled receptors (S1P1-S1P5). S1P1 is crucial to the exit of T-lymphocytes from the thymus and peripheral lymphoid organs through a gradient of S1P. We have previously observed that T-ALL and T-LBL blasts express S1P1. Herein we analyzed the role of S1P receptors in the migratory pattern of human T-cell neoplastic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Traditionally, S1P has been a promoter of chemotaxis for lymphocytes [ 107 ] and a pro-survival signal [ 108 ]. As there is little S1P within tissues, the bulk is found in circulation [ 109 ].…”
Section: Sphingolipid Signaling In Chronic Inflammationmentioning
confidence: 99%
“…Traditionally, S1P has been a promoter of chemotaxis for lymphocytes [ 107 ] and a pro-survival signal [ 108 ]. As there is little S1P within tissues, the bulk is found in circulation [ 109 ].…”
Section: Sphingolipid Signaling In Chronic Inflammationmentioning
confidence: 99%
“…For these studies, we compared luciferase expression with either CART-2 or its non-FTY720-conjugated analogue CART-1 in cell lines expressing or lacking the S1P1 receptor (Figure ). Specifically, the Jurkat and K562 cell lines were used as an S1P1-expressing cellular model, and the CHO cell line was used as a model that naturally lacks expression for S1P1 (Figure S1). 4 h after treatment, mRNA expression was measured as relative bioluminescence of the cells treated with CART/mRNA complexes compared to cells treated with naked Fluc mRNA, which were used as negative controls.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our group showed that S1P induces chemotaxis and chemokinesis of T-cell acute lymphoblastic leukemia (T-ALL) blasts at 100 nM. By contrast, high concentrations of S1P (1000, 5000 and 10,000 nM) induce fugetaxis (or chemorepulsion) of the same cells [ 17 ]. It is thus conceivable that different thymocyte subpopulations present different sensitivity in migratory behavior under S1P stimulation, depending on the concentration and receptor expression, and that VLA-5 expression could differentially influence cell response in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…S1P1 is widely expressed, mainly in endothelial cells, brain, heart and immune cells [ 14 , 15 ]. S1P1 signaling in T cells suppresses proliferation and cytokine production and regulates cell migration [ 9 , 16 ], promoting chemotaxis or fugetaxis depending on the S1P concentration [ 17 ]. Accordingly, several studies demonstrate the essential role of S1P and S1P1 in cell migration and, mainly, in the egress of T cells from the thymus to peripheral lymphoid organs.…”
Section: Introductionmentioning
confidence: 99%